Korban Pembunuhan dalam Prespektif Viktimologi dan Fikih Jinayat - nafi' mubarok (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
The criminal incidents which currently occur in society indicate that many victims of the criminal motion have been continoustly dropping which then cause various suffers of either material or nonmaterial damages. Moreover, they can be possibly enduring a direct and indirect harm,  a physical or psycological harm. Unfortunately, the victims of the criminal incidents got less attention and treatment proportionally and maximally. This condition can be viewed from the legal status of the victims on the criminal and positive law in Indonesia which has not been put equitably or even handless. This fundamental circumstance results two main matters; (1) there is less legal preservation for many victims and, (2) there is less righteous judgement of a judge for the victims, doers or society. Moreover, according to Islamic criminal law (fiqih Jinayat), the victims got the satisfactory rights especially their legal position as the most suffered party. The civic administration system in Indonesia should appearently be updated to be more appreaciative and responsive to the victim’s rights.   It is how the criminal and positive law and the Islamic criminal law in Indonesia try to place the victim’s position proportionally and professionally.